2019
DOI: 10.3390/pharmaceutics11090480
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Eudragit®-Based Electrospun Nanofibrous Mats and Their Formulation into Nanofiber Tablets for the Modified Release of Furosemide

Abstract: Furosemide, a chloride channel blocker ordinarily used as a high-ceiling or loop diuretic, is practically insoluble in water and dilute acids. Due to its acidic nature, furosemide is mostly absorbed in the stomach and in the upper small intestine. Efforts have focused on the development of sustained release systems of furosemide in order to improve the effectiveness of the drug, which exhibits poor aqueous solubility and poor permeability. Recently, electrospun nanofibrous drug delivery systems have emerged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…50 All other ingredients including lyophilized GDD, HP-β-CyD and ES-100 show earlier change around 300 °C. [51][52][53][54] These results indicated that coaxial NFs effectively enhanced the thermal stability of encapsulated GDD.…”
Section: Thermogravimetric Analysismentioning
confidence: 72%
“…50 All other ingredients including lyophilized GDD, HP-β-CyD and ES-100 show earlier change around 300 °C. [51][52][53][54] These results indicated that coaxial NFs effectively enhanced the thermal stability of encapsulated GDD.…”
Section: Thermogravimetric Analysismentioning
confidence: 72%
“…The experiments were performed in two different aqueous media: for the first 2 h, 450 mL of 0.2 M HCl solution (pH 1.2) was used to simulate the stomach pH, and to that 450 mL of 0.14 M K 2 HPO 4 solution (pH 9) was then added, to have the required composition of the next phase, which simulates the enteric pH (pH 6.8, final volume 900 mL). [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This concept has been proven by Shen et al for the non-steroidal anti-inflammatory (NSAID) drug ketoprofen 28 and by Illangakoon and co-workers for the antispasmodic API mebeverine hydrochloride, 29 among other studies. 30,31 pH-sensitivity can also be imparted through the inclusion of a third component into the recipe: the incorporation of sodium bicarbonate has been shown to accelerate drug release in acidic conditions, giving fibres which could be used to target API release to the tumour microenvironment. 32 Thermo-responsive polymers can be included in the ES process, leading to fibres which can respond to temperature.…”
Section: Monoaxial Electrospinning Of Small Molecule Drugsmentioning
confidence: 99%